Child Personality as Moderator of Outcome in a School–based Intervention for Preventing Externalising Behaviour. Issue 3 (May 2013) - Stoltz, Sabine; Prinzie, Peter; De Haan, Amaranta; van Londen, Monique; De Castro, Bram Orobio; Deković, Maja
Studying moderators of intervention effects is essential to elucidate what works for whom. The present study investigated whether child personality moderates short–term and follow–up effects of an individualised preventive school–based intervention for children with externalising behaviour. The sample consisted of 48 schools, with 264 fourth–grade children displaying externalising behaviour (Mage = 10.2 years), randomly assigned to the intervention (n = 191) or no intervention control (n = 73) condition. Teachers and children reported at pretest, posttest and follow–up test about reactive and proactive aggression. Child personality was assessed by teachers at pretest. Child conscientiousness moderated short–term intervention effects, indicating that more organised and planful children benefited more from the intervention. Child extraversion moderated both short–term and follow–up intervention effects, with low extraverted children showing larger effects. These results affirm the importance of including personality as moderator of intervention effects in future studies, as interventions adapted to specific child traits might yield larger effects. Copyright © 2012 John Wiley & Sons, Ltd.